'I'm still here, I'm still alive': Understanding successful aging in the context of HIV. (February 2018) - Solomon, Patricia; Letts, Lori; O'Brien, Kelly K; Nixon, Stephanie; Baxter, Larry; Gervais, Nicole
As people living with HIV (PLWH) live longer, increased understanding of individuals' values and perceptions of successful aging can assist health providers in working with PLWH to set meaningful goals as they age. The purpose of this qualitative study was to understand how PLWH define successful aging and their perceptions of contributors to successful aging. Fourteen men and ten women over the age of 50 years (mean age 57 years; mean time since diagnosis 18 years) participated in individual interviews. Interviews were analyzed using directed content analysis. Six themes emerged: accepting limitations, staying positive, maintaining social supports, taking responsibility, living a healthy lifestyle, and engaging in meaningful activities. The participants emphasized individual control. This highlights the importance of working with PLWH to understand their values and aspirations, and create patient-centered goals. From a research perspective this reinforces calls to include the subjective experiences of older adults in developing successful aging criteria.